Analisis Strategi Marketing Mix pada Esteh Indonesia dalam Perspektif Ekonomi Islam - Umul Qiromah; Sarwo Edy; Sakum; M H Ainulyaqin (Masyarakat Ekonomi Syariah Bogor, 2024)
This study aims to analyze marketing strategies applied to increase brand awareness through social media on Esteh Indonesia beverages Telaga Asih Cikarang branch, in accordance with the perspective of islamic economics. This type of research uses qualitative methods, descriptive research techniques data is collected through observation (observation), interviews, and documentation. The results of this study show that the marketing strategies implemented by Indonesia Iced tea Telaga Asih beverages to increase brand awareness through social media are: 1) products, by selecting high-quality raw materials, designing products in an attractive way, and maintaining high-quality flavors. 2) price, setting a relatively cheap price for everyone to drink it. 3) distribution location, by providing strategic marketing location and unique design for customer convenience. 4) promotion through print browsers and brand awareness through social media. And create daily video content through social media and upload it once a week. From the perspective of islamic economics, the marketing strategy of Esteh Indonesia (Telaga Asih Cikarang branch) apply islamic marketing characteristics that are in line with sharia law, including divinity, morality, reality and humanity as well as islamic marketing principles namely shiddiq (honest), amanah (trustworthy), fatanah (intelligent / leadership) and tabligh (communication).